(untitled) (Journal of actual problems of jurisprudence, 2019)
In this article the author examines the problems of pharmaceutical activities in the Republic of Kazakhstan. The current system of state regulation of the pharmaceutical sector aimed at creating attractiveness of domestic pharmaceutical market in terms of the integration processes taking place. The main problem today is the lack of credit facilities, gaps in the regulatory framework regarding taxes. Speaking about the results of the development and problems of the pharmaceutical sector, we often forget about one of the main conditions for the functioning of the pharmaceutical industry personnel. The problem of providing the pharmaceutical industry experts, relevant to modern market demands requires an urgent solution. Key words: pharmaceutical activity, market, tax law.